Reference and information services an introduction - Cassell, Kay Ann; Hiremath, Uma (ALA Neal-Schuman, 2023)
"The fifth edition of Reference and Information Services: An Introduction is consciously aimed at arming the reference librarian with the skills, expertise, and mindset needed to keep up with changing resources and best practices"--